Time perspective predicts parents education involution perception via education anxiety, expectations for children might not as incomprehensible as it seems - Zhang, Shuyang; Che Hassan, Norlizah; Sulong, Rose Manisah (Human Resource Management Academic Research Society, 2023)
Time is a bird forever on the wing, and parents are always involved in the whole process of their children's growth, like childhood play, school readiness, university choice, and job decisions. In other words, these are part of the child's upbringing process and cannot be separated from parental participation, support, and a forward-thinking plan. Parents with rich social experience and survival wisdom will help children avoid life, study, and work detours in the future. The concept of time is people's understanding and perception of time. It covers people's perception, evaluation, memory, prediction, representation, and planning of time. Philip Zimbardo also mentions five types of time perspectives, including a positive and negative view of time that focuses on the past; a fatalistic and hedonistic view of the time of the moment; and a future view of time. Parents' different time perspectives contain different educational planning and choices when facing children's growth. In the last three years, the public has been interested in China's education revolution phenomenon and the "double reduction" policy, and they want to know whether the "double reduction" policy plays a role in reducing parent education anxiety and whether it has an impact on educational anxiety and choices with different time-period parents. In this research gap, the researchers selected 200 Chinese parents to explore parents’ educational wisdom and choices from the perspective of Philip Zimbardo's time psychology in the face of the "double reduction" policy. Findings highlight the importance of parents’ forward-lookingnes and flexibility in educating their children.